First detection of Cryptosporidium DNA in blood and cerebrospinal fluid of HIV-infected patients - Velásquez, Jorge Néstor (2018)
Fil: Velásquez, Jorge Néstor. Hospital Municipal de Infecciosas Dr. Francisco Javier Muñiz; Argentina.